Evaluation of "College CHEF," a Campus-based, Culinary Nutrition Education Program - Jennifer McMullen; Melinda Ickes; Melody Noland; Don Helme (The Ohio State University Libraries, 2017)
Aim: Evaluate the impact of a campus-based culinary nutrition education program, the College CHEF: Cooking Healthfully Education for Life-long Change, to determine if there were significant differences preto post- intervention with participants' attitudes, behaviors, and knowledge with healthy eating/cooking. Background: College students have high rates of overweight and obesity and tend to have unhealthy dietary practices. Culinary nutrition programs may provide students a means to improve related attitudes, behaviors, and knowledge. Methods: College students residing on campus were recruited. Participants completing both pre- and post-measures were included in analysis: Control (n= 17) and intervention groups (n = 15). Quasi-experimental pre-, post- design: Surveys were administered to both groups at baseline and post-intervention in October-November 2015. Results:  There was a statistically significant improvement in fruit and vegetable consumption (p = .03) and with knowledge of cooking terms and techniques (p < .001). Conclusions:  Campus-based culinary nutrition education programming has potential to positively impact college students' fruit and vegetable consumption and cooking knowledge. Future programs should incorporate strategies such as additional opportunities to engage in hands-on practice and building cross-campus collaborations to promote sustainability.